2005
DOI: 10.1200/jco.2005.66.130
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Temsirolimus (CCI-779), a Novel Inhibitor of mTOR, in Heavily Pretreated Patients With Locally Advanced or Metastatic Breast Cancer

Abstract: In heavily pretreated patients with locally advanced or metastatic breast cancer, 75 and 250 mg temsirolimus showed antitumor activity and 75 mg temsirolimus showed a generally tolerable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
224
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(250 citation statements)
references
References 20 publications
13
224
3
8
Order By: Relevance
“…This model also revealed that the lack of R-Ras2 promotes signalling compensation mechanisms in tumours similar to those seen before on the inactivation of specific PI3K/mTORC route signalling elements [39][40][41][42][43][44][45] . In those cases, such compensation effects are mostly mediated by the elimination of mTORCdependent negative feedbacks on the Raf/Erk route [39][40][41][42][43][44][45] . However, the development of these signatures in MMTVHer2 tg ;Rras2 À / À mice seems to require long-term Darwinian selection events, because primary MECs from both MMTVHer2 tg ;Rras2 À / À (this work) and Rras2 À / À knockout mice 18 do not exhibit such signatures.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 69%
See 1 more Smart Citation
“…This model also revealed that the lack of R-Ras2 promotes signalling compensation mechanisms in tumours similar to those seen before on the inactivation of specific PI3K/mTORC route signalling elements [39][40][41][42][43][44][45] . In those cases, such compensation effects are mostly mediated by the elimination of mTORCdependent negative feedbacks on the Raf/Erk route [39][40][41][42][43][44][45] . However, the development of these signatures in MMTVHer2 tg ;Rras2 À / À mice seems to require long-term Darwinian selection events, because primary MECs from both MMTVHer2 tg ;Rras2 À / À (this work) and Rras2 À / À knockout mice 18 do not exhibit such signatures.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 69%
“…Despite this, the R-Ras2-dependent PI3Ka pool is clearly relevant in vivo, given the marked tumorigenic and metastatic defects shown by R-Ras2-deficient breast cancer cells when implanted in recipient mice. The morphogenetic alterations seen in preneoplasic mammary glands of MMTV-Her2 tg ;Rras2 À / À mice, together with the signalling compensation events detected in tumours arising in those mice, are also indirect evidence in favour of defects in the PI3Ka/Akt/ mTORC route in this experimental model 30,31,[39][40][41][42][43][44][45] . However, as reconstitution experiments are not possible in this case, we cannot formally exclude the possibility that those events could be generated by defects in other R-Ras2-dependent signalling routes (Supplementary Discussion).…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 99%
“…Clinically, rapamycin analogues with advanced stability and pharmacological properties have been well tolerated by patients in Phase I trials, and these agents have shown a hopeful antitumor consequence in breast cancer (Hidalgo and Rowinsky, 2000;Garber, 2001;Chan et al, 2005;Acharya and Sahoo, 2011). However, regardless of the potency of rapamycin in preclinical studies, the clinical development of this drug floundered because of its poor solubility in water (2.6 μgml-) (Simamora et al, 2001), no tumor tissue specificity, low bioavailability and dose limiting toxicity.…”
Section: Rapamycinmentioning
confidence: 99%
“…Temsirolimus (sirolimus 42-ester 2,2-bis hydroxymethyl propionic-acid; CCI-779) is a more water-soluble ester derivative of its parent compound sirolimus, selected for development as an anticancer agent based on its more favourable pharmaceutical characteristics and superior therapeutic index. Temsirolimus has already been tested in phase I and II trials with promising activity and good safety profile (Atkins et al, 2004;Baselga et al, 2004;Raymond et al, 2004;Chan et al, 2005). In phase I studies, rash and mucositis were dose-limiting, and other adverse events (AE) observed include eczematous reactions, dry skin, herpes-type lesions, mild myelosupression, hypercholesterolaemia and hypertriglyceridemia (Atkins et al, 2004;Baselga et al, 2004;Raymond et al, 2004).…”
mentioning
confidence: 99%